PENGARUH FAKTOR PRODUKSI TERHADAP PENGEMBANGAN PERIKANAN TUNA DI KOTA AMBON - Sangadji, Selfi; Mustaruddin, Mustaruddin; Wisudo, Sugeng Hari (Jurnal Teknologi Perikanan dan Kelautan, 2017)
The purpose of the study is to analyze the influence level of the production factors to development of the tuna fishing industry in Ambon City. The data collected are the vessel size, gear size, long trip, fuel use, ice use, fresh water and the number of crew. The data comes from Ambon tuna fishermen. Data collected are primary and secondary data. The analysis used is multiple regression analysis. Multiple regression analysis of the relationship of tuna production gets the value of significance (sig) 0,000. Sig be in the range of beliefs <0.005 means that the regression model can predict the tuna fishery production. Determinant coefficient (R2) of about 0.719 shows the influence of production factors together could explain 71.9% up and down the production of tuna. Base on the significance value of each production factor to production, only the use BBM (X4) and the use of ice cubes (X5) which has a significance value <0.05 (0.000). Use of X5 is influential but has no effect supports the development of tuna in Ambon City. Conclusions taken from this study is the production of factors that influence the production of tuna fisheries in Ambon is the use BBM and the use of ice cubes (X5) which has a significance value <0.05 is 0.000.